Pendidikan Kecakapan Hidup dalam Pengembangan Kompetensi Lulusan Mahasiswa PGMI Memasuki MEA - Juhji Juhji; Khaeroni Khaeroni; Imas Masto'ah; Habudin Habudin (JIP Jurnal Ilmiah PGMI, 2019)
The purpose of this study is to describe students' knowledge and understanding of life skills education; describe the readiness of students to enter the MEA; knowing the relevance of life skills education with the MEA pillars; and knowing the model of life skills education that can be applied to develop the competence of student graduates in entering the MEA. The research subjects were taken purposively as many as 30 students, representing each class. The results of the study show that students' knowledge and understanding of life skills and about the enactment of MEA are still very minimal. The level of sensitivity to the emergence of the dynamics of life skills education to prepare themselves to face the MEA is also still relatively low and the readiness of students to face the MEA also has relevance to the level of knowledge and understanding. For this reason, the strategies that need to be developed are: planning and development of relevant curricula, quality of learning by integrating life skills in all subjects, supporting facilities, foreign language skills, strengthening language laboratories and information and technology that facilitate student access to actual information , and expertise is needed from lecturers to students and apprenticeship programs. Key words: life skills education, development of graduate competency, MEA